2022
DOI: 10.3390/genes13091514
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Nrf2 Induces a Pro-Reductive Stress and Adaptive Cardiac Remodeling in the Mouse

Abstract: Nuclear factor, erythroid 2 like 2 (Nfe2l2 or Nrf2), is a transcription factor that protects cells by maintaining a homeostatic redox state during stress. The constitutive expression of Nrf2 (CaNrf2-TG) was previously shown to be pathological to the heart over time. We tested a hypothesis that the cardiac-specific expression of full length Nrf2 (mNrf2-TG) would moderately increase the basal antioxidant defense, triggering a pro-reductive environment leading to adaptive cardiac remodeling. Transgenic and non-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This assumption stemmed from former results suggesting that in HT29 cells, catechins at 10 µM concentration brought the cellular redox status to the borderline of maintained homeostasis [ 9 ]. Recently it has been shown that a sustained overexpression of nuclear factor, erythroid 2-like 2 (Nrf2)-driven antioxidant transcriptome (involving SRXN1 ) leads to reductive stress in cardiac tissue in vivo [ 36 ], whereas catechins are known modulators of Nrf2 expression [ 37 ]. We hypothesized that in cells exposed to strong antioxidants, the production of antioxidant enzymes is not needed, and as a result, the silencing of expression of some genes, e.g., of SRXN1 , via DNA methylation takes place to maintain proper redox homeostasis, in particular, to prevent pushing cells into reductive stress.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption stemmed from former results suggesting that in HT29 cells, catechins at 10 µM concentration brought the cellular redox status to the borderline of maintained homeostasis [ 9 ]. Recently it has been shown that a sustained overexpression of nuclear factor, erythroid 2-like 2 (Nrf2)-driven antioxidant transcriptome (involving SRXN1 ) leads to reductive stress in cardiac tissue in vivo [ 36 ], whereas catechins are known modulators of Nrf2 expression [ 37 ]. We hypothesized that in cells exposed to strong antioxidants, the production of antioxidant enzymes is not needed, and as a result, the silencing of expression of some genes, e.g., of SRXN1 , via DNA methylation takes place to maintain proper redox homeostasis, in particular, to prevent pushing cells into reductive stress.…”
Section: Discussionmentioning
confidence: 99%
“…57 mTOR and PPARγ also act to upregulate NRF2, 41 and sustained NRF2 activation produces excessive reductive stress with adverse effects on cardiomyopathy. 71,72 The balance of PPARα/PPARγ signalling has important implications for patients with cardiomyopathy (Figure 3). The cardiac expression of PGC-1α, PPARα and downstream effectors is downregulated, but the expression of PPARγ is upregulated, in patients with hypertensive, coronary artery disease or heart failure.…”
Section: Pgc-1𝛂 Is a Convergence Point For Nutrient Surplus And Depri...mentioning
confidence: 99%
“…However, prolonged upregulation of PGC‐1α, RXRα and PPARγ leads to mitochondrial oxidative dysfunction, lipid accumulation, maladaptive hypertrophy and cardiomyopathy, 50,69,70 and experimental diabetic cardiomyopathy is alleviated by PPARγ silencing 57 . mTOR and PPARγ also act to upregulate NRF2, 41 and sustained NRF2 activation produces excessive reductive stress with adverse effects on cardiomyopathy 71,72 …”
Section: Cellular Pathways That Underlie the Mechanism Of Action Of Q...mentioning
confidence: 99%